Health Care System in Transition: Some Aspects of Financing - OMIRBAYEVA, Bibigul S.; BAIZHOLOVA, Raissa A.; NURKHALIYEVA, Dulpariz M. (Journal of Advanced Research in Law and Economics; Vol 8 No 4(26) (2017): JARLE Volume 8 Issue 4(26) Summer 2017, 2017)
The provision of quality health services is an important task for each state. The quality of medical services directly depends on financing of the health system. For most post-Soviet countries, including Kazakhstan, an inefficient and outdated funding model of the industry is characteristic, which worsens the provided medical care. In this regard, the authors study how to implement healthcare financing in Kazakhstan for the period from 2011 to 2015. The analysis of health expenditure in Kazakhstan is given in comparison with the countries of the OECD (Organization for economic cooperation and development) and some CIS (Commonwealth of Independent States). The analysis is based on data from the national health accounts. The analysis of the guaranteed volume of free medical care, analysis of macroeconomic indicators of health and private expenditure were the main problems in funding health care. This paper provides recommendations for the modernization of the financing system of the sector and the importance of public-private partnerships.